The enjoyable online learning model for vocational students during COVID-19 pandemic - Endang Mulyatiningsih; Sri Palupi; Prihastuti Ekawatiningsih; Ambar Rizqi Firdausa; Zalik Nuryana (Institute of Advanced Engineering and Science, 2023)
The COVID-19 outbreak has forced all courses to be carried out online. This study aims to explain the characteristics of an enjoyable online learning model based on the platform, the content, and the learning strategy for vocational students. Data was collected using closed-ended and open-ended questionnaires which were responded to by 110 students in 2019/2020. The closed-ended questionnaire revealed the most preferred learning elements, and the open-ended questionnaire was to clarify their reasons. The data were arranged sequentially from the quantitative data to the qualitative data. The results of the study showed that: i) The preferred online platforms were Moodle, Google Meet, and WhatsApp. They like Moodle because the content is well structured, Google Meet is easily accessible, and WhatsApp is their daily routine application; ii) The learning content consists of two to three resources namely: 6-10 pages of papers, 11-15 pages PowerPoint, and 6-10 minutes videos. Too much content causes a heavy learning burden; iii) Most students preferred the blended learning strategy. The synchronous lectures for 60-75 minutes can motivate them because they can interact with lecturers and other students. Asynchronous lectures are more flexible that can be done anytime and anywhere so that the students become more independent in their learning.